2018
DOI: 10.1021/acsami.8b11428
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Homogeneity Mapping of Epitaxial Graphene on Silicon Carbide

Abstract: Epitaxial graphene is a promising route to wafer-scale production of electronic graphene devices. Chemical vapor deposition of graphene on silicon carbide offers epitaxial growth with layer control but is subject to significant spatial and wafer-to-wafer variability. We use terahertz time-domain spectroscopy and micro four-point probes to analyze the spatial variations of quasi-freestanding bilayer graphene grown on 4 in. silicon carbide (SiC) wafers and find significant variations in electrical properties acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…The features observed in these maps have been reported in the literature in 16,48 , and they can be related to the presence of microscopic defects, such as cracks, and to the presence of growth domain. The measurements are affected by edge effects that span about 1 mm from the edge due to the size of the THz beam, which is estimated to be 0.5 mm in diameter.…”
Section: Evsupporting
confidence: 64%
“…The features observed in these maps have been reported in the literature in 16,48 , and they can be related to the presence of microscopic defects, such as cracks, and to the presence of growth domain. The measurements are affected by edge effects that span about 1 mm from the edge due to the size of the THz beam, which is estimated to be 0.5 mm in diameter.…”
Section: Evsupporting
confidence: 64%
“…We remark that Fermi velocity renormalization effects described here only influence the extracted values of n and µ from THz-TDS measurements (see section 2). As such, previously measured and reported values of σ DC and τ in the literature [15,16,[21][22][23]36,42] are accurate, i.e. not affected by this correction.…”
Section: Discussionmentioning
confidence: 68%
“…Examples of sheet conductivity spectra from as‐grown graphene on sapphire are shown in Figure S10d in the Supporting Information. The sheet conductivity spectra did not follow the classical Drude‐model as previously observed as a reduction was noticed in the sheet conductivity at low frequencies—this indicated that the carriers in graphene did not scatter isotropically but experienced some degree of carrier localization . In such cases, the sheet conductivity was better described by the first term of the phenomenological Drude–Smith model σnormals ω=WnormalD1iωτ 1+c1iωτ where W D is the Drude weight related to the DC sheet conductivity as σ DC = W D (1 + c ), and c is a parameter that can take values from −1 to 0 and describes the degree of carrier localization/backscattering .…”
Section: Methodsmentioning
confidence: 82%
“…The waveforms contained transients from internal reflections within the sapphire substrate. Here, the data from the directly transmitted transients were used to extract the sheet conductivity (σ s (ω) = σ 1 + iσ 2 ) of graphene as σnormals ω=nnormalsap+1Z0 × 1Tnormalfilmω1 where Z 0 is the vacuum impedance, T meas is the ratio of the Fourier transforms of the THz waveforms transmitted through graphene‐covered sapphire and bare sapphire (Figure S10b, Supporting Information), and n sap is the refractive index of sapphire (Figure S10c, Supporting Information) calculated from THz waveforms from bare sapphire relative to air …”
Section: Methodsmentioning
confidence: 99%